Upaya Penurunan Persentase Kecacatan Akibat Bad Handling Issue pada Final Inspection PT. XYZ - Michele Ariani Singgih; Nova Sepadyati; Tan Siu Kwang (Jurnal Titra, 2022)
PT. XYZ is globally recognized as one of the leading furniture manufacturing companies. PT. XYZ was established in 1989 located at Sidoarjo, exports to America. The problems faced is defect percentage at the final inspection (buyer inspection) still exceeds the supposed target and the largest is caused by defects due to bad handling issues. Defects are caused by lack of training also no standards and guidelines for operators related to good handling. The purpose of this study is to find a solution as an attempt to reduce the percentage of weekly defects at the final inspection, especially due to bad handling issues. The method used is DMAIC and 5 Whys Analysis to find root cause. Solutions (standards and sketches) are made based on the 5S principle and visual display. Socialization is also done to increase operator’s knowledge. Control will use a check sheet. The result is that socialization has succeeded in increasing the knowledge of operators about good handling. The conclusion is that module (includes standards) and socialization can be used to achieve the company’s expected goals.